Disruptive Social Work: Forms, Possibilities and Tensions. (11th March 2021) - Feldman, Guy
Abstract: In recent years, a growing literature has rediscovered radical social work and the various forms it takes. In these debates, a key concept that has been developed and deployed is 'resistance'. Studies provide growing evidence for the myriad ways in which social workers engage in resistance activities as part of their everyday practice. However, most of these studies portray resistance as an individualised activity and overlook the role of clients in such activities. Drawing on the concept of 'disruptive power', this article makes the case for what it terms 'disruptive social work', which involves collective resistance activities that disrupt institutions and social relations of everyday life to create meaningful change. After providing a definition of disruptive social work, the article suggests that this practice can be carried out at two levels. At the professional level, social workers occupy an important structural position that allows them to disrupt the workings of the social service system. At the client level, social workers can help their differently positioned clients develop a sense of their own disruptive power and activate it. Examples of disruptive social work are presented throughout the article. It concludes by highlighting the practical and ethical challenges this practice poses for social workers today.